Penerapan Etnomatematika Melalui Permainan Engklek Sebagai Media Pembelajaran Bangun Datar - Lutfiah, Ainul; Fuat, Fuat; Supriyo, Supriyo; Ramadina, Novia Isnaini (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the application of ethnomathematics through the traditional game of engklek as a medium for learning flat shapes in elementary schools. The method used is a qualitative approach with data collection techniques in the form of observation, structured interviews, and tests. The data analysis techniques used include data reduction, data presentation, and drawing conclusions to determine the effectiveness of learning. The research subjects were fourth-grade students at Al-Irsyad Al-Islamiyyah Elementary School. The results showed that students were more enthusiastic and active when learning using the engklek game. After the learning process, 90% of students experienced an increase in their understanding of flat shapes. The engklek game helped students understand geometric shapes in a concrete and enjoyable way, as well as fostering an interest in learning mathematics. Additionally, this approach preserves local culture and improves social skills. Learning becomes more contextual and meaningful. Traditional games have proven to be effective as an alternative learning medium for mathematics, especially in abstract subjects such as geometry.